1979
DOI: 10.1149/1.2129235
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic and Anodic Polarization Phenomena at Platinum Electrodes with Doped CeO2 as Electrolyte: I . Steady‐State Overpotential

Abstract: FAST ELECTRODE REACTIONS 1155 ht time delay between the end of the prepulse and the occurrence of the overpotential minimum (sec) x distance from the electrode surface (cm) ,I overpotential (V) ~]m minimum overpotential value in the ~]-t curve (V) v stoichiometric number of the reaction -% time constant of the double layer (see) 9 a characteristic time of the diffusion-electrode reaction system (sec)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
1
9

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 2 publications
11
105
1
9
Order By: Relevance
“…At high oxygen pressures, the current over-potential curves were found to obey the Butler-Volmer equation which implied a charge transfer (or activation) polarization [28]. Also in this study, it was found that at low oxygen pressure, a limiting-current behaviour resulted which was characteristic of cathodic concentration polarization.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…At high oxygen pressures, the current over-potential curves were found to obey the Butler-Volmer equation which implied a charge transfer (or activation) polarization [28]. Also in this study, it was found that at low oxygen pressure, a limiting-current behaviour resulted which was characteristic of cathodic concentration polarization.…”
Section: Introductionsupporting
confidence: 59%
“…Here O represents the oxidized ~Rg~ species, ne is the number of electrons transferred, and R is the reduced species. This mechanism is modelled [27,28] by the Butler-Volmer equation [30] I (~aF~) (-:~oF~c) ] Je = Jo.e exp RT exp R~ (8) and occurs at the three-phase line and/or at the twophase contact area. In this relation, Jo,e is the exchange current density, e, and ~c are the anodic and cathodic transfer coefficients; r& and r/~ are the anodic and cathodic overpotentials.…”
Section: Rtamentioning
confidence: 99%
“…Existing models [31,32] describing the oxygen transfer reactions at the YSZ-noble metal interface do not predict inductive loops in the impedance spectra [ 15 ]. In wet electrochemistry these inductive (or negative capacitive) effects are frequently encountered and can be described with a two-step electron transfer model in which the intermediate species compete for adsorption sites [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variety of research groups were involved to reveal the gas electrode kinetics. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, in the late 1970s when the author and the co-investigators started studies on the kinetics of solid electrolyte gas electrodes, independent research groups proposed different reaction models and no research group succeeded to explain the performance of fuel cells and chemical sensors under the same theorem.…”
Section: Introductionmentioning
confidence: 99%